The Border Health Consortium of the Californias—Forming a Binational (California–Baja California) Entity to Address the Health of a Border Region: A Case Study - Kozo, Justine; Zapata-Garibay, Rogelio; Rangel-Gomez, María Gudelia; Fernandez, April; Hirata-Okamoto, Ricardo; Wooten, Wilma; Vargas-Ojeda, Adriana; Jiménez, Barbara; Zepeda-Cisneros, Hector; Matthews, Charles Edwards (Frontiers in Public Health, 2018)
The California-Baja California border region is one of the most frequently traversed areas in the world with a shared population, environment and health concerns. The Border Health Consortium of the Californias (the “Consortium”) was formed in 2013 to bring together leadership working in the areas of public health, healthcare, academia, government and the nonprofit sector, with the goal of aligning efforts to improve health outcomes in the region. The Consortium utilizes a Collective Impact framework which supports a shared vision for a healthy border region, mutually reinforcing activities among member organizations and work groups, and a binational executive committee that ensures continuous communication and progress toward meeting its goals. The Consortium is comprised of four binational work groups which address HIV, Tuberculosis, Obesity and Mental Health, all mutual priorities in the border region. The Consortium holds two general binational meetings each year alternating between California and Baja California. The work groups meet regularly to share information, resources and provide binational training opportunities. Since inception, the Consortium has been successful in strengthening binational communication, coordination and collaboration by providing an opportunity for individuals to meet one another, learn about each other systems and foster meaningful relationships. With binational leadership support and commitment, the Consortium could certainly be replicated in other border jurisdictions both nationally and internationally. The present article describes the background, methodology, accomplishments, challenges and lessons learned in forming the Consortium.